School competition and students' entrepreneurial intention: International evidence using historical Catholic roots of private schooling - Oliver Falck; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2010)
School choice research mostly focuses on academic outcomes. Policymakers increasingly view entrepreneurial traits as a non-cognitive outcome important for economic growth. We use international PISA-2006 student-level data to estimate the effect of private-school competition on students' entrepreneurial intentions. We exploit Catholic-Church resistance to state schooling in 19th century as a natural experiment to obtain exogenous variation in current private-school shares. Our instrumental-variable results suggest that a 10 percentage-point higher private-school share raises students' entrepreneurial intentions by 0.3-0.5 percentage points (11-18 percent of the international mean) even after controlling for current Catholic shares, students' academic skills, and parents' entrepreneurial occupation.
Keywords: I20; L33; L26; Z12; 330; private school competition; entrepreneurship; Catholic schools; Privatschule; Katholizismus; Wettbewerb; Bildungsverhalten; Entrepreneurship-Ansatz; Schätzung; Welt